Socioeconomic Justice In The Structures Of Indian Senior Citizen Laws - Sharma, Sourabh (International Journal of Psychosocial Rehabilitation, 2020)
The research topic is "Socio-Economic Justice in the Context of Legislation Relating to Senior Citizens in India," and the researcher hoped to get a conceptual knowledge of two concepts portrayed herein. The first is the idea of Socio-Economic Justice for senior people, and the second is regulation in the form of acts, policies, rules, and regulations for senior people; when the two are read together, they serve to accomplish the study's aims. Human Rights are an integral aspect of Human Dignity, and have been adequately safeguarded by multiple sections of the Indian Constitution, as well as global agreements. The Indian judiciary has repeatedly managed several social interaction concerns by stressing fundamental constitutional principles, especially Articles 14 and 21. India will celebrate its 75th anniversary in 2022, yet the goal of this legislation related to the elderly has yet to be entirely achieved.